Structural Characteristics, Gelling Properties, In Vitro Antioxidant Activity and Immunomodulatory Effects of Rhamnogalacturonan-I Rich Pectic Polysaccharides Alkaline-Extracted from Wax Apple (Syzygium samarangense) - Yue Lu; Siyu He; Zifan Zhao; Changxin Liu; Ye Lei; Mingyu Liu; Qing Zhang; Derong Lin; Yaowen Liu; Shang Lin; Xuesong Lu; Wen Qin (Foods)
To upgrade the utilization of Syzygium samarangense in food industries, the key biological component, i.e., polysaccharide, was extracted from the fruit by alkaline treatment, and its structural characteristics, physicochemical properties, gelling properties and biological activities were investigated. The findings demonstrated that the alkaline-extracted S. samarangense polysaccharide (SSP-AK) predominantly exists as a pectic polysaccharide with a high rhamnogalacturonan-I domain. The monosaccharide composition primarily includes rhamnose, glucuronic acid, galacturonic acid, glucose, galactose, and arabinose. The molecular weight distribution of SSP-AK was characterized by two peaks, with fraction 1 exhibiting a high molecular weight of 7658 kDa and fraction 2 exhibiting a molecular weight of 345.3 kDa. Meanwhile, SSP-AK exhibited excellent rheological behavior and gelling properties upon Ca2+-induced gelation, which may be related to its relatively low degree of esterification of 41.3%. Further studies revealed that higher concentrations of pectin and Ca2+ led to the formation of stronger gels. The SSP-AK gels exhibited superior rheological properties, increased hardness, enhanced water-holding capacity, and a more compact network structure than the other gels. Moreover, SSP-AK exhibited significant in vitro antioxidant activity and immunomodulatory effects, including significantly enhancing the DPPH and ABTS radical-scavenging abilities and production of NO, IL-6, and TNF-α in RAW264.7 cell models. This study enhances the understanding of S. samarangense cell wall polysaccharides and may facilitate their application in the development of functional and health-oriented food products.